2021
DOI: 10.3390/ijerph182312695
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination among Healthcare and Non-Healthcare Workers of Hospitals and Outpatient Clinics in the Northern Region of Slovakia

Abstract: The purpose of this study was to analyse attitudes, motivation, and reasons for hesitancy toward COVID-19 vaccination among healthcare workers (HCWs) in northern Slovakia. A cross-sectional study was conducted between 30 August 2021 and 30 September 2021. An anonymous questionnaire was administered. The study was completed by 1277 employees. Multivariate logistic regression was used to identify predictors of COVID-19 vaccination status. A total of 1076 (84.3%) were vaccinated, and 201 (15.7%) were unvaccinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 21 publications
(25 reference statements)
2
36
0
1
Order By: Relevance
“…All were cross-sectional survey studies, and all asked participants a specific question about whether they agreed with mandatory vaccination for HCWs, and all but one 46 found reasonably high levels support. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Our study used a different approach, asking participants to suggest solutions to sub-optimal SARS-CoV-2 vaccination coverage, and in our study a lower proportion of HCWs favoured mandatory vaccination as a strategy. This is likely to reflect that we did not directly ask participants about mandatory vaccination, as explained above.…”
Section: Discussionmentioning
confidence: 90%
“…All were cross-sectional survey studies, and all asked participants a specific question about whether they agreed with mandatory vaccination for HCWs, and all but one 46 found reasonably high levels support. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Our study used a different approach, asking participants to suggest solutions to sub-optimal SARS-CoV-2 vaccination coverage, and in our study a lower proportion of HCWs favoured mandatory vaccination as a strategy. This is likely to reflect that we did not directly ask participants about mandatory vaccination, as explained above.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the unique working situation and risks faced by nurses, the vaccine refusal rates among nurses remain almost similar to other groups of HCWs and somewhat lower than the general population [11][12][13][14][15][16][34][35][36][37][69][70][71][72][73]. Two recent global reviews found that the rates of COVID-19 vaccine refusal were 22% for college students and 18.9% for trainees/students in healthcare professions [12,71].…”
Section: Discussionmentioning
confidence: 99%
“…These reviews did not specifically provide the proportion of nurses included in their data or the COVID-19 vaccine hesitancy rates exclusively for nurses. Still, and surprisingly, many of these reviews and reports suggest that worldwide, among all HCWs, nurses could have one of the highest hesitancy rates for COVID-19 vaccination [13][14][15][16]. By the last quarter of 2021, some countries around the world started mandating COVID-19 vaccinations for HCWs, including nurses [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging COVID-19 pandemic reactivated the discussion of mandatory vaccination on HCWs due to the fact that they were at high risk for COVID-19 infection [ 29 , 30 , 31 ]. There were already 2,679,563 COVID-19 cases and 7857 deaths reported among HCWs [ 32 ].…”
Section: Introductionmentioning
confidence: 99%